Muscle Fatigue in the Latch-Mediated Spring Actuated Mandibles of Trap-Jaw Ants. (11th June 2022) - Larabee, Fredrick J; Gibson, Josh C; Rivera, Michael D; Anderson, Philip S L; Suarez, Andrew V
Abstract: Muscle fatigue can reduce performance potentially affecting an organism's fitness. However, some aspects of fatigue could be overcome by employing a latch-mediated spring actuated (LaMSA) system where muscle activity is decoupled from movement. We estimated the effects of muscle fatigue on different aspects of mandible performance in six species of ants, two whose mandibles are directly actuated by muscles and four that have LaMSA "trap-jaw" mandibles. We found evidence that the LaMSA system of trap-jaw ants may prevent some aspects of performance from declining with repeated use, including duration, acceleration, and peak velocity. However, inter-strike interval increased with repeated strikes suggesting that muscle fatigue still comes into play during the spring loading phase. In contrast, one species with directly actuated mandibles showed a decline in bite force over time. These results have implications for design principles aimed at minimizing the effects of fatigue on performance in spring and motor actuated systems.